The Inventory of Callous and Unemotional Traits: A Construct-Validational Analysis in an At-Risk Sample. (October 2013) - Berg, Joanna M.; Lilienfeld, Scott O.; Reddy, Sheethal D.; Latzman, Robert D.; Roose, Annelore; Craighead, Linda W.; Pace, Thaddeus W. W.; Raison, Charles L.
The Inventory of Callous and Unemotional Traits (ICU), developed to assess callous/unemotional (CU) traits, has recently experienced increased attention in light of the proposal to add a CU specifier to the conduct disorder diagnosis in DSM-5. In a sample of 70 at-risk adolescents (ages 13-17 years) in the foster care system who received a contemplative intervention program, the present study placed the ICU within a nomological network of correlates, including anxiety, depression, hopefulness, loneliness, and physiological measures of stress (e.g., cortisol). The findings offered some support for the ICU's construct validity, including significant negative associations with measures of compassion toward others. Nevertheless, unexpected substantial positive correlations emerged with multiple measures of psychological distress, raising questions concerning other aspects of the ICU's construct validity. Taken together, results of the current study suggest that rather than assessing a dearth of all major emotions as implied by its name and some previous descriptions, the ICU may be heavily saturated with negative emotionality and global maladjustment.